Potensi Hasil Kedelai sebagai Tanaman Sela pada Pertanaman Cabai Rawit - Pratiwi, Herdina; Purwaningrahayu, Runik Dyah (Proceedings Series on Physical & Formal Sciences, 2021)
Incorporating soybeans as intercrop in chili cultivation is intended to increase the added value of land, therefore the selection of soybean varieties and the use of appropriate spacing is needed to obtain optimal soybean yields. The research was conducted at Installation of Research and Study of Agricultural Technology Muneng, Probolinggo at the first dry season 2020. The study used split plot design with 3 replications. The main plot were three planting patterns, namely: (C1) intercropping chili-soybean with spacing of chili 70 cm x 60 cm and soybeans 30 cm x 15 cm,(C2) intercropping chili-soybean with spacing of double row chilies 120 cm x (40 cm x 60 cm) and soybean 25 cm x 15 cm, (M) monoculture soybean with a spacing of 30 cm x 15 cm as a control. The subplots were four varieties of soybeans, namely: (K1) Dering 1, (K2) Dering 2, (K3) Dering 3, and (K4) Argomulyo. Planting one month old chili with soybean seeds was carried out together. Soybeans were harvested at 90 DAS. Observations of soybean include: growth of plants at 51 and 60 DAS, yield and yield components, plant height, number of harvested plants, number of filled pods, weight of 100 seeds, yield of dry seeds. The results showed that the soybean yield of Dering 2 at cropping pattern C1 gave the best yield and did not differ from the yield by monoculture. The higher of soybean yield was supported by plant height and the number of filled pods per plant. Therefore, Dering 2 has a prospect to be intercropped with chili.